Cloning stone pine (Pinus pinea L.) by somatic embryogenesis - Celestino C.; Carneros E.; Ruiz-Galea M.; Alonso-Blázquez N.; Alegre J.; Toribio M. (Mediterranean stone pine for agroforestry, 2013)
Somatic embryogenesis (SE) is the biotechnology of propagation that enables to put multi-varietal forestry (MVF) into practice. MVF involves the use of genetically tested varieties in plantation forestry, balancing genetic gain with diversity. Embryogenic lines can be cryopreserved in liquid nitrogen while corresponding trees are tested in the field, and those showing genetic superiority can be recovered for mass production of elite plants. The SE process in pines involves the initial outgrowth of embryo-suspensor masses (ESM) from immature zygotic embryos, the establishment of embryogenic cultures capable of further differentiation into somatic embryos, and their germination as somatic seedlings. We reported plant regeneration by SE in stone pine, and further research is in progress to improve the efficiency of the several steps. Induction was obtained at very low frequency (0.4%), and the best embryogenic line and maturation condition yielded 220 mature embryos per gram of ESM. Germination was achieved at 70%, and 35 % of somatic embryos were converted into plants. Suspension cultures offer advantages over semisolid cultures for mass propagation. The establishment of ESMs of stone pine in liquid medium is reported, and the recovery of mature embryos from tissues grown in liquid culture is also described. Current main bottlenecks of SE for implementing MFV in stone pine are the low induction rates and the cessation of growth of converted somatic seedlings.
AGROPINE 2011 International Meeting on Mediterranean Stone Pine for Agroforestery, 2011/11/17-19, Valladolid (Spain)